XXI. Digital Economy Infrastructure Development and the “Belt and Road” Initiative - Zhang, Donghuang (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
This paper explores the strategic role of digital economy infrastructure in the “Belt and Road” initiative, highlighting its impact on regional economic development. It discusses the growth of computing power, data centres, and the challenges and opportunities in building digital infrastructure along the route. The paper concludes that international cooperation and policy support are essential for overcoming challenges and leveraging the potential of the digital economy for mutual growth.